Numerical and Graphical Diallel Analyses of Maize (Zea mays L.) Agronomic and Yield Traits under Well Watering and Water Deficit at Silking - A. M. M. Al-Naggar; M. M. M. Atta; M. A. Ahmed; A. S. M. Younis (Archives of Current Research International, 2016)
The objectives of the present investigation were to determine the type of gene action, heritability and expected genetic advance from selection for agronomic and yield traits of maize under water stress and optimum irrigation and to identify the parents that contain favorable genes for adaptive traits to drought tolerance. Plants from a six-parental diallel cross were grown in the field for two seasons using a randomized complete block design with three replications in two separate experiments; the first under well-watered (WW) conditions and the second under water stress (WS) at silking. Results across seasons showed that variances due to both additive and dominance effects were significant, but the magnitude of dominance was much higher than additive variance for all studied traits under WW and WS, except for ears/plant (EPP) and rows/ear (RPE) under WW. Narrow-sense heritability (h2n) was of small magnitude, but ranged from 0.86% (EPP under WS) to 66.67% (EPP under WW). It was observed that 10 out of 12 characters, showed higher h2n under WW than that under the WS environment, but only two traits, namely anthesis-silking interval (ASI) and barren stalks (BS) exhibited higher estimates of h2n under the water stressed environment. The traits ASI, BS, kernels/row (KPR) and kernels/plant (KPP) showed higher expected selection gain under water-stressed than the non-stressed environment, but the remaining traits showed an opposite trend. The inbred parents L20, L53 and Sk5 carried favorable genes for high grain yield and all of its components (except RPE), short ASI and narrow leaf angle (LANG) under WS. These inbreds would be of great value for future plant breeding programs aiming at improving drought tolerance in maize.